2) Любую триг.функцию можно выразить через tg (x/2)
чтобы короче писать---я обозначу tg (x/2)===T
2 + (1 - T^2) / (1 + T^2) - 2T = 0
2(1 - T) + (1 - T^2) / (1 + T^2) = 0
2(1 - T)(1 + T^2) + (1 - T^2) = 0
(1 - T) * (2 + 2T^2 + 1 + T) = 0
(1 - T) * (2T^2 + T + 3) = 0 D = 1 - 4*2*3 < 0
T = 1
tg (x/2) = 1
x/2 = п/4 + пК
x = п/2 + 2пК
1) корень(3)/2 === cos(30) 1/2 === sin(30)
разделим обе части равенства на 2
cos(30)*sin3x + sin(30)*cos3x = 1/2
sin(3x+п/6) = 1/2
3x+п/6 = п/6 + 2пК 3x+п/6 = 5п/6 + 2пК
3x = 2пК 3x = 2п/3 + 2пК
x = 2п/3К x = 2п/9 + 2п/3К
a^2+a-30=0
a1+a2=-p=-1
a1*a2=q=-30
a1=5
a2=-6
x^2+4=5
x^2=5-4=1
x1=1
x2=-1
x^2+4=-6
x^2=-6-4=-10-посторонний корень.
2)(x^2-8)=a
a^2+3,5a-2=0
D=3,5^2-4*1*(-2)=12,25+8=20,25=4,5^2
a1=(-3,5+4,5)/2*1=1/2
a2=(-3,5-4,5)/2=(-8)
x^2-8=a1=1/2
x^2=1/2+8=0,5+8=8,5
x1=√8,5
x2=-√8,5
x^2-8=a2=-8
x^2=-8+8=0
x=0
3)(1-x^2)=a
a^2-3,7a+2,1=0
D=(-3,7)^2-4*1*2,1=13,69-8,4=5,69=2,3^2
a1=(-(-3,7)+2,3)/2*1=(3,7+2,3)/2=6/2
a1=3
a2=(-(-3,7)-2,3)/2=(3,7-2,3)/2=1,4/2
a2=0,7
1-x^2=a1=3
-x^2=3-1=2
x^2=-2-нет корней
1-x^2=a2=0,7
-x^2=0,7-1=-0,3
x^2=0,3
x1=√0,3
x2=-√0,3
4) (1+x^2)=a
a^2+0,5a-5=0
D=0,5^2-4*1*(-5)=0,25+20=20,25=4,5^2
a1=(-0,5+4,5)/2*1=4/2
a1=2
a2=(-0,5-4,5)/2=(-5)/2
a2=-2,5
1+x^2=a1=2
x^2=2-1=1
x1=1
x2=-1
1+x^2=a2=-2,5
x^2=-2,5-1=-3,5
x^2=-3,5-посторонний корень